Extensive Atrophic Gastritis Increases Intraduodenal Hydrogen Gas - Yoshihisa Urita; Toshiyasu Watanabe; Tadashi Maeda; Tomohiro Arita; Yosuke Sasaki; Takamasa Ishii; Tatsuhiro Yamamoto; Akiro Kugahara; Asuka Nakayama; Makie Nanami; Kaoru Domon; Susumu Ishihara; et al. (Gastroenterology Research and Practice)
Objective. Gastric acid plays an important part in the prevention of bacterial colonization of the gastrointestinal tract. If these bacteria have an ability of hydrogen (H2) fermentation, intraluminal H2 gas might be detected. We attempted to measure the intraluminal H2 concentrations to determine the bacterial overgrowth in the gastrointestinal tract. Patients and methods. Studies were performed in 647 consecutive patients undergoing upper endoscopy. At the time of endoscopic examination, we intubated the stomach and the descending part of the duodenum without inflation by air, and 20 mL of intraluminal gas samples of both sites was collected through the biopsy channel. Intraluminal H2 concentrations were measured by gas chromatography. Results. Intragastric and intraduodenal H2 gas was detected in 566 (87.5%) and 524 (81.0%) patients, respectively. The mean values of intragastric and intraduodenal H2 gas were 8.5±15.9 and 13.2±58.0 ppm, respectively. The intraduodenal H2 level was increased with the progression of atrophic gastritis, whereas the intragastric H2 level was the highest in patients without atrophic gastritis. Conclusions. The intraduodenal hydrogen levels were increased with the progression of atrophic gastritis. It is likely that the influence of hypochlorhydria on bacterial overgrowth in the proximal small intestine is more pronounced, compared to that in the stomach.